PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA PAPAN MULTIFUNGSI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DI KELAS V SD NEGERI 101910 SIDODADI - Yolanda Patricia Panjaitan; Patri Janson Silaban; Irmina Pinem; Juliana; Eka Margareta Sinaga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by a multifunction board media on mathematics learning outcomes of fifth-grade students at SD Negeri 101910 Sidodadi in the 2024/2025 academic year, focusing on the topic of Greatest Common Factor (GCF) and Least Common Multiple (LCM). The research employed a quantitative experimental method with a sample of 35 students. Data collection techniques included pre-tests, post-tests, and questionnaires. The results showed that the students’ average pre-test score was 29.17, categorized as